2010
DOI: 10.1007/s12374-010-9110-2
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression and Inactivation of UGT73B2 Modulate Tolerance to Oxidative Stress in Arabidopsis

Abstract: Glycosyltransferases (GTs) play an important role in modulating solubility, stability, bioavailability, and bioactivity of secondary metabolites, such as flavonoids. In Arabidopsis thaliana, at least 120 family 1 uridine diphosphate (UDP)-glycosyltransferases (UGTs) have been predicted. However, little is known about their substrates or their physiological roles in planta. To define the role of UGT73B2 in planta, we first characterized its expression pattern using transgenic Arabidopsis plants carrying the cis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 29 publications
(30 reference statements)
1
8
0
Order By: Relevance
“…In particular, glycosylation catalyzed by a superfamily of GTs plays significant roles in modulating the solubility, stability, bioavailability and bioactivity of various small molecules [18], 19,41. Recent studies have demonstrated that GTs play important roles in modulating plant tolerance to abiotic stresses [31], [32]. In this study, for the first time, we demonstrated that ectopic expression of the Arabidopsis GT gene UGT85A5 enhanced the adaptation of the transgenic tobacco plants under salt stress.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In particular, glycosylation catalyzed by a superfamily of GTs plays significant roles in modulating the solubility, stability, bioavailability and bioactivity of various small molecules [18], 19,41. Recent studies have demonstrated that GTs play important roles in modulating plant tolerance to abiotic stresses [31], [32]. In this study, for the first time, we demonstrated that ectopic expression of the Arabidopsis GT gene UGT85A5 enhanced the adaptation of the transgenic tobacco plants under salt stress.…”
Section: Discussionsupporting
confidence: 53%
“…DIN2 , P450 , RD20 , ORG1 and PCC1 ) leading to increased tolerance to salinity and drought stress in Arabidopsis thaliana [31]. UGT73B2 loss-of-function endowed the mutant with oxidative stress tolerance [32]. Family 1 are the largest GT family that has various potential substrates from plant secondary metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al . () reported that loss of function of UGT73B2 alone or in conjunction with its closest homologs, UGT73B1 and UGT73B3 , confers greater tolerance of Arabidopsis roots to oxidative stress induced by paraquat. These authors suggested that these UGT genes might play a physiological role in the glycosylation of flavonoids in roots.…”
Section: Discussionmentioning
confidence: 99%
“…; Kim et al . ). However, except for UGT73C6 , which encodes a flavonol‐3‐ O ‐rhamnoside‐7‐ O ‐glucosyltransferase (Jones et al .…”
Section: Introductionmentioning
confidence: 97%
“…For the RNAi construct, the 449-bp fragment of GAL2 that is also conserved for GAZ, GAL1, and GAL3 was amplified with two different sets of primers as listed in Supplemental Table 3. The two fragments were inserted into the pBluescript II SK(+) vector (pBSK-dGUS) to make a hairpin loop after transcription as described previously (Kim et al, 2010). The fragment in pBSK-dGUS was again PCR amplified with a forward primer containing CACC and a reverse primer as listed in Supplemental Table 3.…”
Section: Plasmid Construction and Plant Transformationmentioning
confidence: 99%